2020
DOI: 10.21307/ane-2020-037
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and noradrenaline content and release in the dorsal hippocampus during learning and spatial memory in prenatally stressed rats

Abstract: Prenatal stress causes learning and spatial memory deficits in adulthood by modifying hippocampal function. The dorsal hippocampus contains serotonergic and noradrenergic neuron terminals, which are related to cognitive processes. It is currently unknown whether prenatal stress modifies serotonin (5-HT) and noradrenaline (NA) content and their release in the hippocampus during cognitive performance. Therefore, we measured these variables in the dorsal hippocampus of prenatally stressed males during spatial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Serotonin (5‐hydroxytryptamien [5HT]) is linked to emotional and motivational aspects of human behavior, including mediating stress responses, activation of the HPA axis (Winberg et al., 2001), and learning and memory (Abdul Aziz et al., 2012; Kuramochi & Nakamura, 2009; Meneses, 1998). PS decreased 5‐HT receptor levels in the hippocampus of male offspring (Akatsu et al., 2015; Guerrero et al., 2020; Peters, 1986; Szewczyk et al., 2014). Some studies indicated that 5‐HT1A receptor decreased in both sexes (Gemmel et al., 2016; Huang et al., 2012).…”
Section: Hippocampus and Ps Exposure: A Molecular Perspectivementioning
confidence: 99%
“…Serotonin (5‐hydroxytryptamien [5HT]) is linked to emotional and motivational aspects of human behavior, including mediating stress responses, activation of the HPA axis (Winberg et al., 2001), and learning and memory (Abdul Aziz et al., 2012; Kuramochi & Nakamura, 2009; Meneses, 1998). PS decreased 5‐HT receptor levels in the hippocampus of male offspring (Akatsu et al., 2015; Guerrero et al., 2020; Peters, 1986; Szewczyk et al., 2014). Some studies indicated that 5‐HT1A receptor decreased in both sexes (Gemmel et al., 2016; Huang et al., 2012).…”
Section: Hippocampus and Ps Exposure: A Molecular Perspectivementioning
confidence: 99%
“…Cholinesterase inhibition remains a leading position in the treatment of cognitive impairments observed in Alzheimer's dementia [18]. The role of serotonergic and monoaminergic neurotransmitter systems has been studied [19,20]. The importance of PDEs and their inhibition of learning and memory processes has been less investigated.…”
Section: Introductionmentioning
confidence: 99%